ДИДАКТИЧНІ ЗАСАДИ ОРГАНІЗАЦІЇ ПІЗНАВАЛЬНОЇ ДІЯЛЬНОСТІ СТУДЕНТІВ (Педагогіка вищої та середньої школи, 2008)
In article the interrelation educational and knowledge activity of the students is opened, the features of educational activity of the students from positions activity approach are determined.